2022
DOI: 10.3390/ijms23136897
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Tumor-Transforming Gene 1/Delta like Non-Canonical Notch Ligand 1 Signaling in Chronic Liver Diseases

Abstract: The management of chronic liver diseases (CLDs) remains a challenge, and identifying effective treatments is a major unmet medical need. In the current review we focus on the pituitary tumor transforming gene (PTTG1)/delta like non-canonical notch ligand 1 (DLK1) axis as a potential therapeutic target to attenuate the progression of these pathological conditions. PTTG1 is a proto-oncogene involved in proliferation and metabolism. PTTG1 expression has been related to inflammation, angiogenesis, and fibrogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 164 publications
0
5
0
Order By: Relevance
“…We then tested some proteins that may have contributed to this process in order to thoroughly examine its molecular underpinnings. According to many studies, Dlk1 is identified as a Notch family protein and the best studied noncanonical Notch ligand [ 25 , 26 ], so we first tested Notch1, one of the four Notch receptors, which has been verified to directly interact with Dlk1 in both yeast and mammalian two-hybrid systems [ 27 , 28 ]. Then, we looked at Rhoc, which is a protein that plays a key role in cell migration [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…We then tested some proteins that may have contributed to this process in order to thoroughly examine its molecular underpinnings. According to many studies, Dlk1 is identified as a Notch family protein and the best studied noncanonical Notch ligand [ 25 , 26 ], so we first tested Notch1, one of the four Notch receptors, which has been verified to directly interact with Dlk1 in both yeast and mammalian two-hybrid systems [ 27 , 28 ]. Then, we looked at Rhoc, which is a protein that plays a key role in cell migration [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Its abnormal expression can promote tumor progression[ 58 ]. PTTG1 is a proto-oncogene involved in proliferation, metabolism, cell cycle progression, DNA damage/repair, and apoptosis[ 59 ]. Previous studies have shown that PTTG1 is overexpressed in HCC cell lines and HCC tissues[ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…42 The activation is mediated by focal adhesion kinase (FAK)-MMP9 signaling, p53/21, phosphatidylinositol 3-kinase/protein kinase B (MAPK/ERK), IL-6/ signal transducer and activator of transcription 3 (IL-6/STAT3) signaling pathways, and tumor suppressor phosphatase and tensin homolog deleted on chromosome 10 (PTEN), peroxisome proliferator-activated receptor gamma (PPARγ), nuclear factor kappa-light-chain-enhancer of activated B cells, and toll-like receptors, and recently was associated with the pituitary tumor transforming gene 1 (PTTG1)/delta like non-canonical notch ligand 1 (DLK1) signaling pathway. [43][44][45][46][47][48] When activated, HSCs promote migration, proliferation, and resistance of HCC cells though modulation of TGF-β signaling and MMP9 upregulation. 35,49 Autophagy, an intracellular degradation system and protective mechanism, has recently been shown to be involved in the activation of HSCs.…”
Section: Activation Of Hscsmentioning
confidence: 99%
“…Moreover, DLK1 suppresses PPARγ, which inhibits tumor growth, invasion, and EMT. 46 Multidrug resistance can also be mediated by overexpression of ATP-binding cassette transporters (ABC transporters), which extrude a variety of toxic substances, thus increasing cancer stemness, EMT, and chemoresistance. [108][109][110][111] As a result, ABC transports could be used in research as CSC and chemotherapy markers.…”
Section: Quiescencementioning
confidence: 99%